Cytotoxic Effect of the Alcoholic Extract of Conocarpus erectus Leaves on MDA-MB 231 and MCF7 Breast Cancer Cell Lines - Fathi , Shams Munaf; Ali, Israa Ahmed (Iraqi Journal of Science, 2023)
Currently, there is a growing interest in medicinal plants extracts as some plants have shown antitumor potential. The goal of this study was to test the anticancer activity of methanol extract of Conocarpous erectus leaves in breast cancer cells. Cytotoxicity was tested in vitro on breast cancer cell lines, MCF7 [Estrogen receptor + (ER+)] and MDA-MB231 [Estrogen receptor - (ER-)], in addition to normal fibroblast cells (REF). MTT assay was utilized to measure the growth inhibitory effects after 48 hours exposure to extracts. Viability results indicated that MDA-MB231 were sensitive (GI50 = 56.1µg/ml).However, no sensitivity was seen in both MCF7 and REF cells (GI50>100 µg/ml). Interestingly the sensitivity seen in MDA-MB231 cells was associated with a significant reduction in cell number and size. It can be concluded from this study that leaves extracts may provide a candidate therapy against breast cancer cells and sensitivity was not linked with ER expression. No effect was observed in normal cells.